Identification and Composition of Volatile Compounds in Liquid Smoke Derived from Betara Variety of Areca catechu Husk - Kamalia Muliyanti; Chusnul Hidayat; Supriyadi Supriyadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
The seeds of Areca nut plants hold significant economic value, with a remarkable total production of 65,295.89 tons. However, the husk, constituting 50% to 75% of the fruit, are persistently discarded. This study aims to explore the conversion of Areca nut waste into liquid smoke with specific physical properties and chemical composition. It uses GC-MS to identify volatile chemicals in liquid smoke and carries out a distillation process using a glass column containing natural zeolite for purification. Furthermore, the pyrolysis method is employed at a varying temperature of 150 °C, 250 °C, 350 °C, and 450 °C for 3 hours to process the waste into liquid smoke. The study determines the chemical composition of total acid, phenol, and carbonyl, which range from 1.34% to 3.09%, 0.37% to 0.42%, and 6.84% to 7.46%, respectively. The physical properties of crude liquid smoke in terms of yield range from 16.93% to 31.49%, while the color brightness varies from 25.02 to 57.46. The result shows that liquid smoke comprises 13 acidic, 20 carbonyl, and 6 phenolic compounds, contributing to the aroma. In addition, temperature of the pyrolysis process affects the formation of liquid smoke and the corresponding compounds contained in Areca husk.